2009
DOI: 10.2459/jcm.0b013e328329cb0f
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic approach for urgent abdominal surgery in patients with left ventricular assist devices

Abstract: Despite the fact that the rate of surgical complications mainly related to the necessary anticoagulation has been reported to be significant in patients supported by ventricular assist devices (VADs) who underwent noncardiac surgery, we report two cases showing that adequate peri-operative management of medical therapy and utilization of mini-invasive surgical approaches (i.e. laparoscopy) may limit the risks of morbidity, especially when surgery is required on an urgent basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…This can be avoided by maintaining intraabdominal pressure lower than 10-12 mm Hg. 22 Infection can also be a concern. Antibiotic prophylaxis in accordance with the usual standard for abdominal surgical procedures was used in our patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This can be avoided by maintaining intraabdominal pressure lower than 10-12 mm Hg. 22 Infection can also be a concern. Antibiotic prophylaxis in accordance with the usual standard for abdominal surgical procedures was used in our patients.…”
Section: Discussionmentioning
confidence: 98%
“…24 The most frequently reported complication in these patients is postoperative bleeding due the necessary anticoagulation therapy required for the VAD in order to avoid thromboembolic events. 22,25,26 Many of these patients require hospital admission prior to elective operations and conversion from warfarin to heparin anticoagulation, which can be stopped or reversed in the immediate perioperative period. In emergency procedures, such as with these two patients, transfusion of fresh frozen plasma is required to acutely correct the patient's chronic anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common anesthetic concerns include management of anticoagulation, 15,16 patient monitoring limitations inherent to minimally pulsatile blood flow, 10,17,18 modified surgical access to the operative site, 1923 concern for intraoperative cardiovascular and cerebrovascular events, 2426 management of intraoperative device malfunction, 6 and postoperative complications including bleeding 15,2628 and infection. 2934 …”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, laparoscopic cholecystectomy has been 628679S RIXXX10.1177/1553350616628679Surgical InnovationAshfaq et al shown to be a safe procedure in critically ill cardiac patients, especially patients with MCAD. 6,[9][10][11][12] The aim of our study was to evaluate the safety and feasibility of laparoscopic surgery in patients with MCADs.…”
Section: Introductionmentioning
confidence: 99%